ANALISIS JABATAN PADA BAGIAN TATA USAHA (STUDI KASUS UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG) - Hatii, Amelia Tuffa; Sabur, Ambuy; Wahab, Andi Yustira (Journal of Business Education and Social, 2022)
Job Analysis in the Administrative Section of the Sheikh Yusuf Islamic University Case Study This research was conducted at the Sheikh Yusuf Islamic University Tangerang. This study aims to determine the extent of Administrative Positions in the Faculty of Economics, FKIP, Postgraduate Program. This research uses Observation, Interview, and Documentation. In the case study research, Spadley did not use the term population, but called it "social situation" or a social situation consisting of three elements, namely: place, actor, and activity that interact synergistically. This social situation can be stated as an object of research that wants to be understood in more depth "what happened" in it. In descriptive research it does not use populations, because descriptive research departs from certain cases that exist in certain social situations and the results of the study will not be applied to the population, but transferred to other places in social situations that have similarities with the situations in the cases studied. Samples in descriptive research are not called respondents, but as informants, or participants, informants, and teachers in the research. The sample in qualitative descriptive research is also not called a statistical sample, but a theoretical sample, because the purpose of descriptive research is to generate theory.